Enhancing Creative Thinking in Physics Education: A Systematic Review and Meta-Analysis - Fauziah Rasyid; Heru Kuswanto; Supahar Supahar; Jayanti Kharisma Putri; Wahyu Dilla Abdullah; Sul Daeng Naba; Iqbal Ainur Rizki (Kasuari: Physics Education Journal (KPEJ), 2026)
Creative thinking is a critical skill in physics education that enables students to develop effective problem-solving. This study aims to explore various interventions and their effects on enhancing creative thinking skills in physics education through a systematic review and meta-analysis. A keyword search across Scopus and ERIC identified 22 studies that met the criteria and were selected for analysis. The meta-analysis findings indicate that interventions implemented in physics learning significantly enhance creative thinking skills, with a very strong effect size. Among the types of interventions, instructional models demonstrated the largest effect size, highlighting their potential to foster creative thinking. Moderator analysis revealed significant variations across countries of study, sample size, intervention duration, and the physics topics involved. However, no significant differences were found for moderators such as publication type, education level, types of interventions applied, and instruments measuring creative thinking. These findings emphasise the importance of designing and adapting teaching strategies to enhance creative thinking skills in physics learning. This study contributes to strengthening the evidence for integrating creative thinking into physics education to meet the demands of the 21st century.